IMPLEMENTASI PROGRAM PELAYANAN TERPADU SATU PINTU PADA DPMPTSP KABUPATEN PUNCAK JAYA - Soleman Sineri, Sadrak; Aedah, Nur (Universitas Cenderawasih, 2023)
One One-Stop Integrated Service (PTSP) is a policy instructed by the Ministry of Home Affairs to improve public services through the role of local governments. This research aims to analyze the implementation of the PTSP program at the One-Stop Investment and Integrated Service Office (DPMPTSP) of Puncak Jaya Regency in accordance with the Minister of Home Affairs Regulation No. 138 of 2017. This program includes licensing and non-licensing services. With a qualitative approach and descriptive method, this research uses Edward III's policy implementation theory which includes aspects of communication, resources, disposition, and bureaucratic structure. The data collection techniques used are observation, interview, and documentation. Data analysis techniques are in the form of data reduction stages, data presentation, and conclusion drawing and verification. The results showed that communication aspects, such as socialization, had gone well. Human resources are managed by a competent workforce, although the number is limited. Disposition related to program responsibility rests with the DPMPTSP director. In the aspect of bureaucratic structure, permit processing is carried out according to the applicable SOP. A supporting factor for program implementation is the delegation of authority from the regent to the head of DPMPTSP. However, the limited number of human resources is an obstacle to program optimization. The implementation of the PTSP program in Puncak Jaya Regency is considered quite optimal in licensing services. This research confirms the importance of increasing human resources to support program sustainability and improve the quality of public services.